2013
DOI: 10.5812/jjm.5439
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Enteropathogenic <italic>Escherichia coli</italic> (EPEC) From Raw Milk in Kermanshah by Polymerase Chain Reaction (PCR)

Abstract: Background: Infectious diarrhoeal diseases cause major problems throughout the world and are responsible for considerable morbidity and mortality. Enteropathogenic Escherichia coli (EPEC) may cause infantile diarrhoea among children in developing countries. Objectives: The aim of this study was to define the prevalence of EPEC strains in raw milk samples. Materials and Methods: Raw milk samples collected from various cow farms in Kermanshah, Iran, during the period of 22nd June to 22nd September 2009 and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
7
4
0
Order By: Relevance
“…The present study also revealed an overall prevalence of 14.29% for Shiga toxin-producing E. coli O157:H7 (EHEC). This nding was almost in agreement with reports [73] (10.2%), [61] (10.4%), [74] (10.4%), [75] (10.9%), [76] (11.43%), [77] (17.47%), and [71] (18%). But, it was higher than the ndings of [78] (0.54%), [64] (1.92%), [79] (2.1%), [65] (2.4%), [80] (2.4%), [68] (2.9%), [81] (3.38%), [57] (3.5%), [82] (4.2%), [67] (5.2%), [58] (5.4%), [83] (6.3%), [84] (8.8%), [85] (9%), [60] (9.1%), and [86] (9.3%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study also revealed an overall prevalence of 14.29% for Shiga toxin-producing E. coli O157:H7 (EHEC). This nding was almost in agreement with reports [73] (10.2%), [61] (10.4%), [74] (10.4%), [75] (10.9%), [76] (11.43%), [77] (17.47%), and [71] (18%). But, it was higher than the ndings of [78] (0.54%), [64] (1.92%), [79] (2.1%), [65] (2.4%), [80] (2.4%), [68] (2.9%), [81] (3.38%), [57] (3.5%), [82] (4.2%), [67] (5.2%), [58] (5.4%), [83] (6.3%), [84] (8.8%), [85] (9%), [60] (9.1%), and [86] (9.3%).…”
Section: Discussionsupporting
confidence: 92%
“…However, the highest level of resistance was observed against Amoxicillin (95.8%) which was in line with the reports of [60] (100%), and [78] (100%). In addition, 41.7% of the isolates were resistant to Tetracycline which was in agreement with the reports of [59] (47.6%) but was higher than the ndings of [92] (4%), [73] (5.1%), [77] (23.08%), [60] (27.7%), and [93] (32%). However, it was lower than the ndings of [81] (80.6%), [68] (81.8%), [67] (63.63%), and [91] (60.61%).…”
Section: Discussionsupporting
confidence: 89%
“…Based on the results, 10% of all milk and dairy product samples showed EPEC contamination. In another study in Iran, 17 out of 206 (8.25%) raw milk samples were positive for EPEC [ 42 ]. Moreover, in a study conducted in Brazil, a prevalence of 22.1% was reported for EPEC in pasteurized milk isolates [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to state that the E. coli serogroups found in this study have been identified in humans to cause severe infections including fatal cases of infantile gastroenteritis (24). They have also been isolated from animals (dogs, rabbits, monkeys, sheep, birds) and food items such as vegetables and other food products from animal source such as raw milk or cheese (24,25). Barbosa and others recorded an overall prevalence of 43% EPEC serogroup from water and fresh fish in Brazil (9).…”
Section: Discussionmentioning
confidence: 85%